2014
DOI: 10.1021/jz402609d
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Scale Identification of Coexisting Graphene Structures on Ni(111)

Abstract: Through a combined scanning tunneling microscopy (STM) and density functional theory (DFT) approach, we provide a full characterization of the different chemisorbed configurations of epitaxial graphene coexisting on the Ni(111) single crystal surface. Top-fcc, top-hcp, and top-bridge are found to be stable structures with comparable adsorption energy. By comparison of experiments and simulations, we solve an existing debate, unambiguously distinguishing these configurations in high-resolution STM images and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 40 publications
18
92
0
Order By: Relevance
“…Previous studies based on X-Ray Photoemission Spectroscopies (XPS) detected two energetically degenerate attachment conformations of graphene on Ni(111) [9], the so-called bridge-top and top-fcc chemisorbed conformations. The possible identification of these arrangements by Scanning Tunneling Microscopy (STM) was suggested from theoretical predictions in that study and confirmed in a subsequent study by high-resolution STM [10]. Other conformations, such as hcp-fcc, imply that graphene is detached (physisorbed) over the Ni(111) surface [9].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies based on X-Ray Photoemission Spectroscopies (XPS) detected two energetically degenerate attachment conformations of graphene on Ni(111) [9], the so-called bridge-top and top-fcc chemisorbed conformations. The possible identification of these arrangements by Scanning Tunneling Microscopy (STM) was suggested from theoretical predictions in that study and confirmed in a subsequent study by high-resolution STM [10]. Other conformations, such as hcp-fcc, imply that graphene is detached (physisorbed) over the Ni(111) surface [9].…”
Section: Introductionmentioning
confidence: 68%
“…Note that experimentally bridge-top and top-fcc are detected by XPS [9], or observed by STM [10], although a particular preference of one against the other is not clear, so they should be considered as essentially isoenergetic. Nevertheless, a small preference of bridge-top was suggested by XPS data, although this claim must be kept with great caution.…”
Section: Fig 2 Graphically Shows the Accuracy Of The Tested Methods mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] From the electronic point of view, the relatively strong interaction 20,30 between Ni(111) and graphene leads to hybridization between graphene π and Ni 3d orbitals, resulting in band-gap opening. 20,23,35,36 Coherently with π states hybridization, charge redistribution occurs, implying electron accumulation close to the G surface.…”
mentioning
confidence: 99%
“…For example, different chemisorbed configurations of epitaxial graphene coexist on single crystal Ni (111) such as top-fcc, top-hcp, and top-bridge [51]. In addition, there are structural defects [52] [53] in graphene which significantly influence its physical and chemical properties [54].…”
Section: Atomic Structurementioning
confidence: 99%